The Biotechnology of Ugba, a Nigerian Traditional Fermented Food Condiment - Olasupo, Nurudeen A.; Okorie, Chimezie P.; Oguntoyinbo, Folarin A. (Frontiers in Microbiology, 2016)
Legumes and oil bean seeds used for the production of condiments in Africa are inedible in their natural state; they contain some anti-nutritional factors especially undigestible oligosaccharides and phytate. Fermentation impact desirable changes by reducing anti-nutritional factors and increasing digestibility. Ugba is an alkaline fermented African oil bean cotyledon (Pentaclethra macrophylla) produced by the Ibos and other ethnic groups in southern Nigeria. Seen as a family business in many homes, its preparation is in accordance with handed-down tradition from previous generations and serves as a cheap source of plant protein. Its consumption as a native salad is made possible by fermentation of the cotyledon for 2–5 days, but could also serve as a soup flavoring agent when fermentation last for 6–10 days. The fermentation process involved is usually natural with an attendant issue of product safety, quality and inconsistency. The production of this condiment is on a small scale and the equipment used are very rudimentary, devoid of good manufacturing procedures that call to question the issue of microbial safety. This paper therefore reviews the production process and the spectrum of microbial composition involved during fermentation. In addition, potential spoilage agents, nutritional and biochemical changes during production are examined. Furthermore, information that can support development of starter cultures for controlled fermentation process in order to guarantee microbiological safety, quality and improved shelf life are also discussed.